The Role of Medication Adherence Companions on the Pharmacotherapy Outcomes of Hypertensive Patients at Bambanglipuro Community Health Center - Diki Aprianto A; Eva Nurinda; Ari Susiana Wulandari; Ade Puspitasari; Ifa Aris Suminingtyas (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Hypertension is a prevalent chronic condition in primary health care, particularly among geriatric patients requiring long-term therapy. Despite the availability of antihypertensive medications, achieving target blood pressure remains challenging and is often associated with poor medication adherence. Medication Adherence Companions (PMO) may improve adherence and enhance therapeutic outcomes. This study aimed to analyze the role of PMO in the pharmacotherapy outcomes of hypertensive patients at the Bambanglipuro Community Health Center. This analytic observational study with a cross-sectional design involved 101 geriatric patients diagnosed with hypertension. Data were collected using structured questionnaires covering patient characteristics, presence of PMO, medication adherence, and blood pressure control status. Data were analyzed descriptively and using multivariate logistic regression with a significance level of p < 0.05. The results showed that 64.4% of patients had a PMO, and 54.5% demonstrated high adherence. Patients with high adherence were more likely to achieve controlled blood pressure. Multivariate analysis revealed that the presence of PMO significantly increased the likelihood of controlled blood pressure (AOR = 2.77; 95% CI: 1.29–5.95; p = 0.009). Combination therapy was also significantly associated with blood pressure control (AOR = 2.25; p = 0.047). These findings suggest that Medication Adherence Companions can support successful hypertension pharmacotherapy among geriatric patients in primary health care settings.